Spain organises for victory - Comorera, Joan, 1895-1958 ; Campbell, J. R. (John Ross), 1894-1969; Hernández, Jesús, 1907-1971 (London : Communist Party of Great Britain, 1937)
1937 SA14-010-006 90 pages ; 19 cm. 15X/2/103/188